OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY CHARACTERISTICS OF POLYPOIDAL CHOROIDAL VASCULOPATHY SECONDARY TO CHRONIC CENTRAL SEROUS CHORIORETINOPATHY. Issue 9 (September 2019) - Peiretti, Enrico; Iovino, Claudio; Sacconi, Riccardo; Caminiti, Giulia; Querques, Giuseppe
Abstract : Purpose: To report diagnostic capability of optical coherence tomography angiography (OCTA) in detecting polypoidal choroidal vasculopathy and its morphologic characteristics in white patients with chronic central serous chorioretinopathy. Methods: Retrospective consecutive series of 20 eyes (17 consecutive patients) with a diagnosis of polypoidal choroidal vasculopathy secondary to chronic central serous chorioretinopathy based on clinical and multimodal imaging were included. All patients underwent a complete ophthalmologic examination, including best-correct visual acuity, fundus autofluorescence, fluorescein and indocyanine green angiography, spectral-domain optical coherence tomography, and OCTA. Results: In all eyes (100%), OCTA revealed the branching vascular network as a hyperflow lesion in both choriocapillaris and outer retina layers. Segmentation of the choriocapillaris in OCTA, in correspondence of the polypoidal dilation detected at indocyanine green angiography, showed a hyperflow round structure in 75% of cases and hypoflow round structure in 15%. Two of 20 eyes (10%) had no detectable polyps on OCTA. Conclusion: Optical coherence tomography angiography is a noninvasive imaging modality allowing a good visualization of both branching vascular network and polyp dilations. Our findings suggest that OCTA is a useful tool in the investigation of chronic central serous chorioretinopathy complicated by polypoidal choroidal vasculopathy. Abstract : Polypoidal choroidal vasculopathy can occur in patients with chronic central serous chorioretinopathy. Optical coherence tomography angiography seems to be a valuable tool in detecting neovascular branching and aneurysmatic dilatations compared with multimodal imaging.